Three Versions of Crow Omens - Zysk, Kenneth G. (History of Science in South Asia, 2022)
This paper examines three versions of crow omens composed in Sanskrit verses of anuṣṭubh metre from two different sources, one Brahmanic, Gārgīyajyotiṣa, and the other Buddhist, Śārdūlakarṇāvadana. Their similarities in language and content leave little doubt that they had a common source that was probably located in the northwest of the Indian sub-continent sometime around the beginning of the Common Era.